Role of Remote Sensing in Urban Planning and Smart City Development in India - Jain, Anshul; Garg, Chinar (Urban Planning and Construction, 2025)
Rapid urbanization in India, driven by population growth and economic expansion, has intensified challenges such as unplanned sprawl, resource strain, environmental degradation, and inadequate infrastructure. The Smart Cities Mission, launched in 2015, seeks to address these issues by fostering sustainable, technology-driven urban environments across 100 selected cities. Remote sensing (RS) technologies, including satellite imagery (e.g., Landsat, IRS series, high-resolution platforms), play a pivotal role in enabling evidence-based urban planning and smart city initiatives. RS facilitates accurate mapping of land use/land cover changes, monitoring urban expansion, detecting illegal encroachments, and assessing green cover dynamics over time. Integrated with Geographic Information Systems (GIS), it supports multi-layer spatial analysis for infrastructure planning, transportation optimization, flood risk assessment, urban heat island identification, and sustainable resource management. In the Indian context, RS contributes to baseline data creation for master plans, performance monitoring under the Smart Cities Mission (via dashboards and observatories), and predictive modeling of growth patterns to guide resilient development. By providing cost-effective, repetitive, and synoptic data, RS enhances decision making, promotes transparency, and aids in achieving sustainable urban goals. This article examines key applications, case examples from Indian cities, technological advancements, policy frameworks, and future prospects, underscoring RS as an indispensable tool for transforming Indian cities into inclusive, efficient, and environmentally balanced smart urban ecosystems.